Potential Drug Interactions in Outpatients with Hypertension and Comorbid Type 2 Diabetes Mellitus at Arifin Achmad Regional General Hospital Riau Province - Husnawati, Husnawati; Rusnedy, Rahmayati; Fadillah, Ma'isyatul; Zulfitri, Reni (Journal of Food and Pharmaceutical Sciences, 2026)
Hypertension and diabetes mellitus are degenerative diseases that if not managed properly will lead to other disease complications. This condition can cause polypharmacy which has the potential to cause drug interactions. The purpose of this study is to determine the presence or absence of drug interactions used in the treatment of hypertension patients with comorbidities of type 2 diabetes mellitus at Arifin Achmad Hospital, Riau ProvinceThis study was conducted using a descriptive analysis design by collecting retrospective data. The samples are all outpatients diagnosed with hypertension and coexisting type 2 diabetes mellitus from January to December 2024 who met the inclusion criteria. The total sample in this study was 110 samples. In this study use one variable, drug interaction. The instrument used in this study was a patient’s medical record. The results obtained were analyzed descriptively with online media screening using Drugs.com and Medscape.com sites and textbook screening such as Stockley's Drug Information Handbook (DIH) Drug Interaction, 12th edition, 2019. The data obtained were analyzed descriptively using percentages. The results showed that there were 70 cases of potential drug interactions. The type of pharmacodynamic interaction was 100% and based on severity there were major interactions of 1,43%, moderate 92,86% and minor 5,71%. These findings indicate the potential for drug interactions in outpatients with hypertension and comorbid type 2 diabetes mellitus, particularly pharmacodynamic interactions.